2016
DOI: 10.21649/akemu.v21i4.761
|View full text |Cite
|
Sign up to set email alerts
|

Modified Scleral Buckling With a Non-Contact Wide Angle Viewing System and a 25g Chandelier Endoillumintor

Abstract: Purpose:To evaluate the outcome of scleral buckling surgery using a wide angle non-contact viewing system and chandelier endoillumination for per-operative fundus visualization in patients with non-complex rhegmatogenous retinal detachments.Materials and Methods:This was a prospective, interventional study carried out at the Department of Ophthalmology, Mayo Hospital Lahore over a period of six months. Non-probability convenience sampling technique was employed. Fifteen eyes of fifteen pati-ents underwent modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Although similar observations were noted in our group, buckling under the microscope still had its challenges. Jahangir et al [ 21 ] reported difficulty in rotating the globe with the chandelier light in place. Also, Seider et al [ 22 ] noted that the sutures around the muscles did not provide the same control provided with instruments within sclerotomies in PPV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although similar observations were noted in our group, buckling under the microscope still had its challenges. Jahangir et al [ 21 ] reported difficulty in rotating the globe with the chandelier light in place. Also, Seider et al [ 22 ] noted that the sutures around the muscles did not provide the same control provided with instruments within sclerotomies in PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Fixing the silicone band to the sclera before inserting the chandelier trocar and cannula could minimize the risk of these complications. This sequence was used by Jahangir et al [ 21 ] and Wang et al [ 28 ] and also by our group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in band length of 10% to 20% its circumference is considered to be safe, 14 yet many of the reported complications can be attributed to overtightening of the strap. During scleral buckling, the desired indentation effect is checked intraoperatively through the use of binocular indirect ophthalmoscopy or other viewing systems, 18 which is an inadequate qualitative approach given that the appearance of the indentation can be misleading. In contrast, the method described here improves application of the scleral buckle by using objective measurements, resulting in a predictable postoperative buckle height and indentation.…”
Section: Discussionmentioning
confidence: 99%